Rapid and early changes in morphology and gene expression in soya bean seedlings emerging in the presence of neighbouring weeds. (25th April 2016) - Mckenzie‐Gopsill, A G; Lee, E; Lukens, L; Swanton, C J
Summary: Light signalling is an important mechanism of plant competition during the early stages of seedling development. Far‐red‐enriched (FR‐E) light reflected from neighbouring weeds has been shown to induce the shade avoidance response leading to changes in plant morphology and increased variability in yields. In this study, the morphological and molecular changes occurring at the hypocotyl arch and primary leaf stage of soya bean development were investigated in response to FR‐E light reflected from neighbouring weeds. A reduction in the root/shoot was identified at the hypocotyl arch stage, and an increase in height was detected at the unifoliate stage of soya bean seedlings. In addition, FR‐E light induced a change in the expression profile of reactive oxygen species (ROS)‐scavenging genes. Early in seedling development, ROS‐scavenging genes were upregulated. However, this trend was reversed at later stages of development with downregulation of several ROS‐scavenging genes. These results demonstrated the rapidity of induction of the shade avoidance response and that gene expression in soya bean seedlings was dependent upon developmental stage and tissue type sampled.